2014
DOI: 10.1002/cssc.201300945
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum‐Catalyzed Deoxydehydration of Vicinal Diols

Abstract: The commercially available (NH4 )6 Mo7 O24 and other molybdenum compounds are shown to be viable substitutes for the typically employed rhenium compounds in the catalytic deoxydehydration of aliphatic diols into the corresponding alkenes. The transformation, which represents a model system for the various hydroxyl groups found in biomass-derived carbohydrates, can be conducted in an inert solvent (dodecane), under solvent-free conditions, and in a solvent capable of dissolving biomass-derived polyols (1,5-pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 28 publications
(11 reference statements)
3
111
0
Order By: Relevance
“…A third more challenging solution would be to add small, equimolar amounts of the diol and the reductant gradually, which would ensure that the diol concentration is kept so low that the reaction is constantly in the "acceleration" regime; it is simultaneously necessary to keep the diol concentration sufficiently high to prevent an irreversible deactivation of the catalyst, presumably by reduction to catalytically inactive Re nanoparticles. [17] From an economic point of view, the scarcity and high cost of Re [57] makes it a challenge to use a Re-based catalyst for large amounts of biomass, but the direct proof for catalyst deactivation by the substrate shown here for Re could, nonetheless, be an equally important issue for the other transition metals (Mo [39,58] and V [59] ) that have been used as DODH catalysts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A third more challenging solution would be to add small, equimolar amounts of the diol and the reductant gradually, which would ensure that the diol concentration is kept so low that the reaction is constantly in the "acceleration" regime; it is simultaneously necessary to keep the diol concentration sufficiently high to prevent an irreversible deactivation of the catalyst, presumably by reduction to catalytically inactive Re nanoparticles. [17] From an economic point of view, the scarcity and high cost of Re [57] makes it a challenge to use a Re-based catalyst for large amounts of biomass, but the direct proof for catalyst deactivation by the substrate shown here for Re could, nonetheless, be an equally important issue for the other transition metals (Mo [39,58] and V [59] ) that have been used as DODH catalysts.…”
Section: Discussionmentioning
confidence: 97%
“…Upon oxidation of the internal aliphatic diols 4,5-octanediol [8] and cis-1,2-cyclohexanediol [10] (i.e., diols that contain two secondary OH groups), the diketones 4,5-octanedione and 1,2-cyclohexanone were formed. That said, the Mo-catalyzed DODH of 1,2-hexanediol that uses the diol itself as reductant leads to the oxidative deformylation of the diol and the formation of pentanal and formaldehyde; [39] this reactivity has not been observed for Re.…”
mentioning
confidence: 97%
“…[13] However, it is much more difficult to selectively remove OH groups with these catalysts from substrates with four or more OH groups such as erythritol, xylitol, and sorbitol. [15][16][17][18][19][20][21][22][23][24][25] In combination with the hydrogenation of the produced alkene, deoxydehydration transforms two vicinal OH groups to H atoms, and the reaction can be regarded as simultaneous hydrodeoxygenation (Scheme 1). On the other hand, Re, V, and Mo homogeneous catalysts, especially Re, have been reported to be active in deoxydehydration (didehydroxylation) of vicinal OH groups to give alkenes.…”
mentioning
confidence: 99%
“…Whereas Re, V, and Mo catalysts have been reported to be active in the removal of both hydroxyl groups of cyclic vicinal diols, selective removal of one hydroxyl group is not possible with these catalysts. [11][12][13][14][15][16][17] In addition, most of these systems are homogeneous and use reductants other than H 2 . We recently reported that the heterogeneous Ir-ReO x /SiO 2 catalyst was effective in the hydrogenolysis of cis-1,2-cyclohexanediol to cyclohexanol (75 % selectivity); [18] However, the Ir-ReO x /SiO 2 catalyst also cleaved CÀO bonds in the ring structure.…”
Section: Introductionmentioning
confidence: 99%